Efficacy of ultrasound-guided high-intensity focused ultrasound (USgHIFU) for uterine fibroids: an observational single-center study. (10th September 2021) - Marinova, Milka; Ghaei, Shiwa; Recker, Florian; Tonguc, Tolga; Kaverina, Olga; Savchenko, Oleksandr; Kravchenko, Dmitrij; Thudium, Marcus; Pieper, Claus C.; Egger, Eva K.; Mustea, Alexander; Attenberger, Ulrike; et al.
Abstract: Introduction: To evaluate treatment response of uterine fibroids after ultrasound guided high-intensity focused ultrasound (USgHIFU) with a special focus on fibroid size and characterization based on Funaki classification scheme, as well as clinical response to treatment of leading fibroid-associated symptoms. Materials and methods: Uterine fibroids treated by USgHIFU were assigned to Funaki type 1–3 based on T2-w-MRI. Differences in size, non-perfused volume ratio (NPVR) and volume reduction over time were determined using T1-/T2-w MRI sequences and contrast-enhanced sonography. Treatment effects on three leading fibroid-associated symptoms were also evaluated. Measurements were compared by mixed model, Bland–Altman's plot and Spearman's correlation. Results: In this prospective single-center study, 35 patients with 44 symptomatic uterine fibroids were treated by USgHIFU ( n = 22, n = 12 and n = 10 assigned to Funaki type 1, 2 and 3, respectively). NPVRs of Funaki type 1 and 2 fibroids were significantly higher compared to type 3 ( p = .0023). A significant fibroid shrinkage was observed independent of Funaki type compared to baseline: 38.8 ± 26.9%, 46.7 ± 30.3% and 54.5 ± 29.3% at 3, 6 and 12 months, respectively (each p < .05). Moreover, patients experienced a significant improvement of fibroid-associated hypermenorrhea (3.9 ± 1.3 vs. 2.3 ± 1.3), pressure in the pelvic area (3.5 ± 1.3 vs. 2.1 ± 0.9) and frequent urination (2.8 ± 1.5 vs. 1.9 ± 0.8) one year post-procedure (each p < .05), regardless of fibroid Funaki type. Conclusion: Following USgHIFU, a significant shrinkage of uterine fibroids and improvement of leading fibroid-associated symptoms were demonstrated regardless of the Funaki type.